The antiviral compound remdesivir potently inhibits RNA-dependent RNA polymerase from Middle East respiratory syndrome coronavirus - Gordon, Calvin J.; Tchesnokov, Egor P.; Feng, Joy Y.; Porter, Danielle P.; Götte, Matthias (The Journal of biological chemistry, 2020)
Antiviral drugs for managing infections with human coronaviruses are not yet approved, posing a serious challenge to current global efforts aimed at containing the outbreak of severe acute respiratory syndrome–coronavirus 2 (CoV-2). Remdesivir (RDV) is an investigational compound with a broad spectrum of antiviral activities against RNA viruses, including severe acute respiratory syndrome–CoV and Middle East respiratory syndrome (MERS–CoV). RDV is a nucleotide analog inhibitor of RNA-dependent RNA polymerases (RdRps). Here, we co-expressed the MERS–CoV nonstructural proteins nsp5, nsp7, nsp8, and nsp12 (RdRp) in insect cells as a part a polyprotein to study the mechanism of inhibition of MERS–CoV RdRp by RDV. We initially demonstrated that nsp8 and nsp12 form an active complex. The triphosphate form of the inhibitor (RDV-TP) competes with its natural counterpart ATP. Of note, the selectivity value for RDV-TP obtained here with a steady-state approach suggests that it is more efficiently incorporated than ATP and two other nucleotide analogs. Once incorporated at position i, the inhibitor caused RNA synthesis arrest at position i + 3. Hence, the likely mechanism of action is delayed RNA chain termination. The additional three nucleotides may protect the inhibitor from excision by the viral 3′–5′ exonuclease activity. Together, these results help to explain the high potency of RDV against RNA viruses in cell-based assays.